Evaluation of Visual Pathways in Children with Neuronal Ceroid Lipofuscinosis: Diffusion Tensor Imaging Findings - Hafize Otcu Temur; Bahar Atasoy; Gözde Yeşil Sayın; Akın İşcan; Alpay Alkan (Archives of Basic and Clinical Research)
Objective: The aim of our study is to evaluate whether there were any diffusion tensor imaging (DTI) parameter changes in the visual pathways in children with neuronal ceroid lipofuscinosis (NCL) for the early detection of visual pathway damage.